INFLUENCE DES PARAMETRES PHYSICO-CHIMIQUES DE L'EAU SUR LA COMPOSITION ET LA DIVERSITE DES MICRO-INVERTEBRES PEUPLANT LE BARRAGE DE AIN DALIA (WILAYA DE SOUK-AHRAS, NORD-EST ALGERIE) - Bennacer Manel (My University, 2025)
This work is part of an ecosystem-based approach aimed at assessing the ecological quality of the waters of the Aïn Dalia dam (Souk Ahras Wilaya) through the combined analysis of physico-chemical variables and the structure of micro-invertebrate (zooplankton) communities. The study was conducted at ten stations distributed along the dam between January and May 2025. The measured physico-chemical parameters (temperature, pH, electrical conductivity, dissolved oxygen, and turbidity) allowed for the characterization of the aquatic environment and the identification of spatio-temporal variations influencing biotic composition. Concurrently, the analysis of zooplankton assemblages revealed a total of 15 taxa, overwhelmingly dominated by the species Polyarthraremata, which accounted for 87.17% of the individuals recorded. Other taxa such as Asplanchnaherrickii and Cyclopoida also stood out due to their occurrence frequency exceeding 50%. In contrast, some genera like Keratellacochlearis, Cyclops sp., or Daphnia longispina exhibited a more localized or sporadic distribution. A few rare taxa (Harpacticoida, Bosminaleydigii, Lepadella sp.) were observed in only one or two stations, indicating a very limited distribution. The results confirm that zooplankton composition is closely linked to local environmental conditions and emphasize the importance of these organisms as biological indicators in the ecological monitoring of aquatic environments. This study contributes to expanding knowledge of planktonic biodiversity in artificial reservoir ecosystems and offers perspectives for the integrated assessment of water quality in continental aquatic ecosystems. ------------------------------------------------------------------------------------------------------------------------------------------ يندرج هذا العمل في إطار مقاربة إيكولوجية تهدف إلى تقييم الجودة البيئية لمياه سد عين دالية (ولاية سوق أهراس) من خلال التحليل المشترك للمتغيرات الفيزيائية والكيميائية وبنية المجتمعات الحيوية للكائنات اللافقارية المجهرية "العوالق الحيوانية". وقد أنجزت الدراسة على مستوى عشر محطات موزعة على طول السد، خلال الفترة الممتدة من جانفي إلى 2025 ماي سمحت المعايير الفيزيائية والكيميائية المقاسة ( درجة الحرارة الأس الهيدروجيني، التوصيلية الكهربائية، الأوكسجين المنحل والعكارة بتوصيف البيئة المانية وتحديد التغيرات المكانية والزمانية التي تؤثر على التركيب الحيوي بالتوازي كشفت دراسة العوالق الحيوانية عن تسجيل 15 تصنيفا (Taxons) مختلفا، كانت تهيمن عليها بشكل كبير النوعPolyarthraremata، بنسبة بلغت 87.17% من إجمالي الأفراد المعاينين. كما برزت أصناف أخرى مثلAsplanchnaherrickiiوCyclopoidaبتكرار ظهور تجاوز 50 % من العينات في المقابل، لوحظ توزيع موضعي أو عرضي لأنواع أخرى مثل Cyclops sp. KeratellacochlearisLepadellaBosminaleydigiiHarpacticoidaأما الأصناف النادرة على غرارDaphnialongispina. sp، فقد تم رصدها في محطة أو محطتين فقط، مما يعكس انتشارًا محدودًا للغاية. تؤكد النتائج المحصل عليها الارتباط الوثيق بين تركيبة العوالق الحيوانية والظروف البيئية المحلية، وتبرز أهمية هذه الكائنات كمؤشرات بيولوجية في تتبع الحالة الإيكولوجية للأنظمة المانية. وتسهم هذه الدراسة في إثراء المعارف حول التنوع الحيوي للعوالق الحيوانية في البيئات المانية الاصطناعية، وتفتح آفاقا لتقييم متكامل لجودة المياه في النظم البيئية الداخلية. -------------------------------------------------------------------------------------------------------------------------------------------- Ce travail s'inscrit dans une approche écosystémique visant à évaluer la qualité écologique des eaux du barrage de Aïn Dalia (Wilaya de Souk Ahras) à travers l'analyse conjointe de variables physico-chimiques et de la structure des communautés des micro-invertébrés (zooplanctons). L'étude a été menée sur dix stations réparties le long du barrage, entre janvier et mai 2025. Les paramètres physico-chimiques mesurés (température, pH, conductivité électrique, oxygène dissous et turbidité) ont permis de caractériser l'environnement hydrique et d'identifier les variations spatio-temporelles influençant la composition biotique. Parallèlement, l'analyse des peuplements zooplanctoniques a révélé un total de 15 taxons, dominės très largement par l'espèce Polyarthraremata, représentant 87,17% des individus recensés. D'autres taxons tels que Asplanchnaherrickii et les Cyclopoida se sont également distingués par leur fréquence d'occurrence supérieure à 50%. En revanche, certains genres comme Keratellacochlearis, Cyclops sp., ou Daphnialongispina ont présenté une distribution plus localisée ou accidentelle. Quelques taxons rares (Harpacticoida, Bosminaleydigii, Lepadella sp.) n'ont été observés que dans une ou deux stations, traduisant une répartition très restreinte. Les résultats obtenus confirment que la composition du zooplancton est étroitement liée aux conditions environnementales locales et soulignent l'importance de ces organismes comme indicateurs biologiques dans le suivi écologique des milieux aquatiques. Cette étude contribue à enrichir les connaissances sur la biodiversité planctonique en milieu de retenue artificielle et offre des perspectives pour l'évaluation intégrée de la qualité des eaux dans les écosystèmes aquatiques continentaux.
Keywords: Micro-invertebrates; Physico-chemical parameters; Ain Dalia Dam; Algeria. اللافقاريات الدقيقة المعايير الفيزيائية والكيميائية، سد عين دالية الجزائر. Micro-invertébrés; Paramètres physico-chimiques; Barrage Ain Dalia; Algérie